A comparison of a new multinomial stopping rule with stopping rules of fleming and gehan in single arm phase II cancer clinical trials - Goffin, John R (BioMed Central, 2011)
BACKGROUND: Response rate (RR) alone may be insensitive to drug activity in phase II trials. Early progressive disease (EPD) could improve sensitivity as well as increase stage I stopping rates. This study compares the previously developed dual endpoint stopping rule (DESR), which incorporates both RR and EPD into a two-stage, phase II trial, with rules using only RR. METHODS: Stopping rules according to the DESR were compared with studies conducted under the Fleming (16 trials) or Gehan (23 trials) designs. The RR hypothesis for the DESR was consistent with the comparison studies (r(alt )= 0.2, r(nul )= 0.05). Two parameter sets were used for EPD rates of interest and disinterest respectively (epd(alt), epd(nul)): (0.4, 0.6) and (0.3, 0.5). RESULTS: Compared with Fleming, the DESR was more likely to allow stage two of accrual and to reject the null hypothesis (H(nul)) after stage two, with rejection being more common with EPD parameters (0.4, 0.6) than (0.3, 0.5). Compared with Gehan, both DESR parameter sets accepted H(nul )in 15 trials after stage I compared with 8 trials by Gehan, with consistent conclusions in all 23 trials after stage II. CONCLUSIONS: The DESR may reject H(nul )when EPD rates alone are low, and thereby may improve phase II trial sensitivity to active, cytostatic drugs having limited response rates. Conversely, the DESR may invoke early stopping when response rates are low and EPD rates are high, thus shortening trials when drug activity is unlikely. EPD parameters should be chosen specific to each trial.